2011
DOI: 10.1021/sb200003v
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of MreB Filaments on Liposome Membranes: A Synthetic Biology Approach

Abstract: The physical interaction between the cytoskeleton and the cell membrane is essential in defining the morphology of living organisms. In this study, we use a synthetic approach to polymerize bacterial MreB filaments inside phospholipid vesicles. When the proteins MreB and MreC are expressed inside the liposomes, the MreB cytoskeleton structure develops at the inner membrane. Furthermore, when purified MreB is used inside the liposomes, MreB filaments form a 4-10 μm rigid bundle structure and deform the lipid ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 32 publications
2
100
0
1
Order By: Relevance
“…The aim is to set-up a close to native E. coli system to test synthetic gene circuits and to develop an artificial cell. This system enabled the assembly of the bacterial actin MreB on membranes after cell-free transcription/translation inside large liposomes [65]. Furthermore, it was shown that the presence of MreC is required to obtain filamentous structures (Figure 6a,b).…”
Section: Cell-like Systemsmentioning
confidence: 99%
“…The aim is to set-up a close to native E. coli system to test synthetic gene circuits and to develop an artificial cell. This system enabled the assembly of the bacterial actin MreB on membranes after cell-free transcription/translation inside large liposomes [65]. Furthermore, it was shown that the presence of MreC is required to obtain filamentous structures (Figure 6a,b).…”
Section: Cell-like Systemsmentioning
confidence: 99%
“…Some researchers have attempted to mimic this function by directly polymerizing cytoskeleton components encapsulated in lipid vesicles (obtained via conventional approaches; figure 5a) [69][70][71][72]. Others have encapsulated hydrogels within lipid vesicles to mimic cytoskeleton deformation and viscoelastic properties [73,74] (figure 5b).…”
Section: Artificial Cytoskeletonsmentioning
confidence: 99%
“…Au-delà de l'encapsulation, la construction d'une membrane active est un défi. Des (Figure 3) [55][56][57]. La réalisation de fonctions plus complexes comme la division ou la réplication de l'ADN semble encore lointaine.…”
Section: Les Systèmes Acellulaires D'expression Comme Plateforme Expéunclassified